Biological Invasions in Marine Ecosystems - Rilov, Gil (Springer, 2017)
Biological invasions are considered to be one of the greatest threats to the integrity of most ecosystems on earth. This volume explores the current state of marine bioinvasions, which have been growing at an exponential rate over recent decades. Focusing on the ecological aspects of biological invasions, it elucidates the different stages of an invasion process, starting with uptake and transport, through inoculation, establishment and finally integration into new ecosystems. Basic ecological concepts - all in the context of bioinvasions - are covered, such as propagule pressure, species interactions, phenotypic plasticity, and the importance of biodiversity. The authors approach bioinvasions as hazards to the integrity of natural communities, but also as a tool for better understanding fundamental ecological processes. Important aspects of managing marine bioinvasions are also discussed, as are many informative case studies from around the world.